A Cahn-Hilliard Type Equation with Gradient Dependent Potential (Journal of Partial Differential Equations, 2008)
We investigate a Cahn-Hilliard type equation with gradient dependent potential. After establishing the existence and uniqueness, we pay our attention mainly to the regularity of weak solutions by means of the energy estimates and the theory of Campanato Spaces.
Keywords: Cahn-Hilliard equation; existence; uniqueness; regularity